2018
DOI: 10.1016/j.biotechadv.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Screening of organic solvents for bioprocesses using aqueous-organic two-phase systems

Abstract: The application of conventional organic solvents has been essential in several steps of bioprocesses in order to achieve sufficient economic efficiency. The use of organic solvents is frequently used either to partly or fully replace water in the reaction medium or as a process aid for downstream separation. Nowadays, manufacturers are increasingly requested to avoid and substitute solvents with hazardous potential. Therefore, the solvent selection must account for potential environmental hazards, health and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 154 publications
(155 reference statements)
0
33
0
Order By: Relevance
“…The solvent screening for the biphasic reaction was carried out in a biphasic system containing a Na 2 HPO 4 -citric acid buffer containing 200 mM of FA and different organic solvents for 2 and 6 h. As shown in Figure 4, the highest molar conversion yield (100%) of 4-VG was obtained in 1-octanol after 6 h of reaction, followed by n -octane, whose conversion yield reached up to 95%. Moreover, from safety, health, and environmental protection perspectives, 1-octanol is preferable to the other organic solvents tested (Grundtvig et al, 2018). Therefore, 1-octanol was selected as the organic solvent used in the subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solvent screening for the biphasic reaction was carried out in a biphasic system containing a Na 2 HPO 4 -citric acid buffer containing 200 mM of FA and different organic solvents for 2 and 6 h. As shown in Figure 4, the highest molar conversion yield (100%) of 4-VG was obtained in 1-octanol after 6 h of reaction, followed by n -octane, whose conversion yield reached up to 95%. Moreover, from safety, health, and environmental protection perspectives, 1-octanol is preferable to the other organic solvents tested (Grundtvig et al, 2018). Therefore, 1-octanol was selected as the organic solvent used in the subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al (2009) reported that 21.3 g/L (141.9 mM) of 4-VG (95% conversion yield) was obtained by using E. coli harboring a FA decarboxylase from B. pumilus in 1L of an octane–aqueous two-phase system. These issues such as low yield and product concentrations are mainly caused by the toxicity of the substrate, product, and organic solvents and enzymatic inactivation (Tomek et al, 2015; Grundtvig et al, 2018). Although water-immiscible organic solvents were used in the biphasic system, trace solvents dissolved in the aqueous phase may have serious inhibitory effects on the biocatalysts (Doukyu and Ogino, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore initiated our enzyme studies by surveying a panel of commercially available KREDs from Codexis Inc. against ketone 1 a for reduction and DKR activity (see electronic Supporting Information for screening details). The enzyme KRED‐P2‐C02 handily afforded γ‐lactone 2 a and was subsequently subjected to a broader selection of biphasic solvent conditions (Figure ) . Scale‐up of the screening hits found that, with minor additional optimization, biphasic solvent conditions with a clear partition between organic and aqueous phases predominated.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, enzyme recovery is eased, reaction equilibria can be shifted toward the desired products and enantioselectivity is enhanced for several enzymes. [ 1,2 ]…”
Section: Introductionmentioning
confidence: 99%